The Development of Virtual Scenario Simulation-Based Learning Model to Enhance Practice Skills of Nursing Students in Maternal and Newborn Nursing and Midwifery: Ranida Thiraphalawat - Thiraphalawat, Ranida; Charoenwong, Ziwapon (Princess of Naradhiwas University Journal, 2024)
The development of virtual scenario simulation-based learning model to enhance practice skills of nursing students in Maternal and Newborn Nursing and Midwifery .The objectives of this research and development were to: 1) develop a virtual scenario simulation-based learning model to enhance practice skills of nursing students in Maternal and Newborn Nursing and Midwifery; 2) evaluate the effectiveness and feasibility of the program; and 3) compare the learning achievement of knowledge, and practice skills and satisfaction of nursing students before and after participating in the virtual scenario simulation-based learning program. There were three phases of this research. First phase was study and analyze situation of using a virtual scenario simulation-based learning. Fifteen experts were selected as samples using the purposive sampling method. A questionnaire for interviews was utilized to obtain data. To develop virtual scenario simulation-based learning model in phase two, the information from the interview questionnaire was examined. After the instrument’s quality was validated by five experts, 66 third-grade nursing students from Police Nursing College were divided into two groups: 33 individuals were assigned to the experimental group and 33 individuals to the control group. The samples were used to compare knowledge, practice skills, and satisfaction after utilizing virtual scenario simulation-based learning in phase three. Findings revealed the following: 1. The development of virtual scenario simulation-based learning model to enhance practice skills of nursing students in Maternal and Newborn Nursing and Midwifery consisted of five components included: 1) instructor; 2) learner; 3) practical course administration; 4) virtual scenario simulation-based learning design; and 5) learning outcomes. 2.The feasibility of virtual scenario simulation-based learning model demonstrated the highest level (M = 4.88, S.D. = 0.26) 3.The effectiveness of virtual scenario simulation-based learning model shown the highest level (M= 4.58, S.D.= 0.35) 4.The experiment group’s learning scores of post-test was 6.50 (S.D. = 1.52), the control group’s learning scores of post-test was 5.67 (S.D. = 1.03), the average satisfaction score was 4.23 (S.D. = 0.33), and the average practice skill score was 4.33 (S.D. = 0.12)